IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT PADA PENGEMBANGAN SISTEM INVENTORY GUDANG BERBASIS WEB DI CV MALANG PACKAGING - Nataliya, Sukma; Alexius Endy Budianto; Heri Santoso (Prodi Teknik Informatika, Fakultas Sains dan Teknologi, 2025)
Data inventory system is needed for decision making regarding the amount of raw materials to be produced or restocked back to the warehouse. And the obstacle that often occurs in Malang Packaging is the amount of remaining goods that are different and cause the number of goods produced to be messy, sometimes lacking or excess. This is because the recording of stock items still uses manual methods. From the above obstacles, a system is needed that can process inventory data in a computerized manner so that recording can be done more quickly, precisely and accurately. Data collection methods carried out using several methods such as observation, interviews and literature studies. The design and design of the application itself uses the Rapid Application Development (RAD) method as a system development method. The system developed is web-based with the PHP programming language. And the data retrieval connection will be connected to MySQL dabatase. The supporting software used is Sublime Text and Xampp. It is hoped that with this website-based inventory system, it will make it easier for users to monitor data on goods in the warehouse and help reduce errors in recording the number of goods in and out.